Markups and Concentration in the Context of Digitization: Evidence from German Manufacturing Industries - Weche, John P.; Wagner, Joachim (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Recent empirical studies suggest that there is a rising trend of market power across sectors in advanced economies. We contribute to this line of research by providing industry-specific evidence for German manufacturing industries, based on representative high-quality firm level data from official statistics that cover firms from all size classes with more than 20 employees (2005–2013). We compare firm-specific markups and industry concentration as market power indicators and discuss the role of digitization. Our results do not suggest an overall average increase in market power in German manufacturing. However, if we look at changes in individual industries, then we do find increasing markups and an increasing concentration in many industries. We also demonstrate the ambiguous relationship between the two indicators and find no clear evidence that digital transformation and market power go hand in hand.
Keywords: Market Power; Business Concentration; Markups; Digitalization; Manufacturing; Germany; 330 Wirtschaft